Answer: m = -3
Step-by-step explanation:
The polynomial expression
(mx+8)(2x−4)
The next step is to expand the bracket
(mx × 2x) + (mx × -4) + (8×2x) + (8× -4)
2mx^2 - 4mx + 16x -32
2mx^2 - 4mx + 16x -32
2mx^2 + 12x -32 - - - - - - - - - - 1
From the question,
The expression is simplified to
−6x2+28x−32 - - - - - - - - - - - - 2
This means equation 1 = equation 2
Comparing both equations, we have
2mx^2 = −6x^2
2m = -6
m = -6/2 = -3
The correct option is a
The expression becomes
(-3x+8)(2x−4)
Let us check
Expanding the brackets,
(-3x × 2x) + (-3x ×-4)+ (8×2x) + (8×-4)
= -6x^2 +12x + 16x - 32
= -6x^2 +18x - 32